2020
DOI: 10.3390/s20113205
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Novel Inverted Rocker Orthoses for First Metatarsophalangeal Joint on Gastrocnemius Muscle Electromyographic Activity during Running: A Cross-Sectional Pilot Study

Abstract: Background: The mobility of the first metatarsophalangeal joint (I MPTJ) has been related to the proper windlass mechanism and the triceps surae during the heel-off phase of running gait; the orthopedic treatment of the I MPTJ restriction has been made with typical Morton extension orthoses (TMEO). Nowadays it is unclear what effects TMEO or the novel inverted rocker orthoses (NIRO) have on the EMG activity of triceps surae during running. Objective: To compare the TMEO effects versus NIRO on EMG triceps surae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“… 8 , 12 The total amount of the decreases reported in the present work was larger when wearing CMW than NSO perhaps because of the more powerful effect of hard CMW on PL tendon strain and its muscle belly relief than that obtained via cushioning NSO. As has been reported previously with running shoes 29 and novel orthoses, 34 it seems that wearing cushioning (vs hard materials) may induce more muscle activity in order to balance the foot during running gait.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“… 8 , 12 The total amount of the decreases reported in the present work was larger when wearing CMW than NSO perhaps because of the more powerful effect of hard CMW on PL tendon strain and its muscle belly relief than that obtained via cushioning NSO. As has been reported previously with running shoes 29 and novel orthoses, 34 it seems that wearing cushioning (vs hard materials) may induce more muscle activity in order to balance the foot during running gait.…”
Section: Discussionsupporting
confidence: 63%
“…Sample size estimations to carry out the present study were assessed by the statistics unit at the Complutense University of Madrid, which used SPSS Version19.0 (IBM Corp) software to compare the EMG changes in PL activity during running among the 7 different study conditions. Data on the gastrocnemius lateralis in a previous study 34 showed a mean EMG value of 25.96 ± 4.68 mV for a novel orthosis compared with 22.27 ± 2.51 mV ( P < .05) for typical running shoes. Considering a statistical power of 80%, β = 20%, a 95% confidence interval, and α = .05, a total of 30 participants were needed to perform this study.…”
Section: Methodsmentioning
confidence: 83%
See 2 more Smart Citations
“…Our surprising results could mean that following reach the joint stop movement through ME´s thickness, the pulling force needed to perform the Jack´s test was the same, regardless of external ME´s restrictions. The total amount of dorsal mobility of the rst ray in WRP reported by previous studies was set at 4.9mm 17 , which is higher than that achieved in the ankle dorsi exion position; this is due to the increased tension on the plantar aponeurosis related to the Windlass mechanism 12,18 as it has been shown previously by the intrinsic correlation between rst MPJ and the triceps surae 27,39 . The ME thicknesses used in our experiment were 2, 4, and 8 mm; in our results, the 4-mm ME orthotic produced the greatest tension effort on the rst MPJ, which could be compared with the mobility results of Grady 17 , but without any statistical signi cance.…”
Section: Discussionmentioning
confidence: 83%